Investigating Thomas Hardys reaction to Victorian religious forces through reading Tess of the DUrbervilles and Jude the Obscure - Sivandipour, Faezeh; Talif, Rosli (Universiti Putra Malaysia Press, 2014)
The Victorian era during the nineteenth century was marked by the Church of England and was greatly associated with “Victorian values,” strict rules, formal manners, rigidly defined roles and highly moralistic standards of behaviour. Considering the main religious thoughts of that period, this study examines the basic religious notions of the time which had an effect on Thomas Hardy and provoked him to question the existing religious and social forces of the time through Tess of the D’Urbervilles(1891) and Jude the Obscure (1895). Due to his many bitter and tragic stories, most readers consider him a pessimist writer—a description that he himself does not agree. Rather, Hardy considers himself a ‘meliorist’; therefore, he cannot accept being a pessimist. It is significant to note the religious clues in his two mentioned novels, which help the reader to see a reflection of his inner beliefs and his religious outlook on his characters as well. This article, based for the most part on several quotations of the two novels, attempts to extrapolate religious and social problems of the Victorian age and the way Thomas Hardy responds to the so-called Victorian notions through considering his emphasis on repeating the consequences of these forces in the selected novels.